2015
DOI: 10.1016/j.scitotenv.2015.06.097
|View full text |Cite
|
Sign up to set email alerts
|

Deep-ocean foraging northern elephant seals bioaccumulate persistent organic pollutants

Abstract: As top predators in the northeast Pacific Ocean, northern elephant seals (Mirounga angustirostris) are vulnerable to bioaccumulation of persistent organic pollutants (POPs). Our study examined a suite of POPs in blubber (inner and outer) and blood (serum) of free-ranging northern elephant seals. For adult females (N=24), we satellite tracked and sampled the same seals before and after their approximately seven month long foraging trip. For males, we sampled different adults and sub-adults before (N=14) and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 68 publications
3
9
0
Order By: Relevance
“…Highly lipid soluble POPs can disseminate through the food chain by collecting in body fat and biomagnifying, or increasing in concentration as they move from one organism to another. For example, the northern elephant seal is a “marine mammal predator” at the top of the food chain that contains massive concentrations of environmental contaminants that are primarily stored in AT (249) (99) (250) (318) (2). Measurements of bioaccumulation in fish and other aquatic organisms is often reported as the bioconcentration factor (BCF), which is defined as the extent to which a chemical concentration in an aquatic organism exceeds the chemical concentration in surrounding water (206).…”
Section: Physico-chemical Properties and Lipids Influence At Pop Bioamentioning
confidence: 99%
“…Highly lipid soluble POPs can disseminate through the food chain by collecting in body fat and biomagnifying, or increasing in concentration as they move from one organism to another. For example, the northern elephant seal is a “marine mammal predator” at the top of the food chain that contains massive concentrations of environmental contaminants that are primarily stored in AT (249) (99) (250) (318) (2). Measurements of bioaccumulation in fish and other aquatic organisms is often reported as the bioconcentration factor (BCF), which is defined as the extent to which a chemical concentration in an aquatic organism exceeds the chemical concentration in surrounding water (206).…”
Section: Physico-chemical Properties and Lipids Influence At Pop Bioamentioning
confidence: 99%
“…Serum, inner blubber, and outer blubber samples from all elephant seals had detectable concentrations of ΣDDTs, ΣPCBs, ΣCHLs, and ΣPBDEs. The concentrations of POPs used in this study for northern elephant seal serum, inner blubber, and outer blubber have been reported previously (Peterson et al 2015), although a summary of medians and ranges of POP concentrations can be found in Table 1. The specific equations to predict POP concentrations in one tissue from POPs concentrations in another tissue for all compounds are found in Table 2 and specific statistical results are found in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…We used standard procedures for chemical immobilization and collection of blubber and blood from northern elephant seals (Le Boeuf et al 2000, Robinson et al 2012, and these procedures have been described previously in Peterson et al (2015). In brief, a full-thickness blubber core was collected from the lateral pelvic area of each seal from a sterile scalpel incision with a 6 mm biopsy punch (Miltex, Inc., York, Pennsylvania, USA) and stored in aluminum foil.…”
Section: Animal Samplingmentioning
confidence: 99%
See 2 more Smart Citations